The changing landscape of smoldering multiple myeloma: A european perspective - Caers, J.; de Larrea, C.F.; Leleu, X.; Heusschen, R.; Zojer, N.; Decaux, O.; Kastritis, E.; Minnema, M.; Jurczyszyn, A.; Beguin, Y.; Wasch, R.; Palumbo, A.; et al. (Oncologist, 2016)
Smoldering multiple myeloma (SMM) is an asymptomatic clonal plasma cell disorder and bridges monoclonal gammo- pathyof undetermined significance to multiple myeloma (MM), based on higher levels of circulating monoclonal immunoglobulin and bone marrow plasmocytosis without end-organ damage. Until a Spanish study reported fewer MM-related events and better overall survival among patients with high- risk SMM treated with lenalidomide and dexamethasone, prior studies had failed to show improved survival with earlier intervention,although a reduction in skeletal-related events (without any impact on disease progression) has been described with bisphosphonate use. Risk factors have now been defined, and a subset of ultra-high-risk patients have been reclassified by the International Myeloma Working Group as MM, and thus will require optimal MM treatment, based on biomarkers that identify patients with a >80% risk of progression. The number of these redefined patients is small (~10%), but important to unravel, because theirriskof progression to overt MM is substantial ($80% within 2 years). Patients with a high-risk cytogenetic profile are not yet considered for early treatment, because groups are heterogeneous and risk factors other than cytogenetics are deemed to weight higher. Because patients with ultra-high- risk SMM are now considered as MM and may be treated as such, concerns exist that earlier therapy may increase the risk of selecting resistant clones and induce side effects and costs. Therefore, an even more accurate identification of patients who would benefit from interventions needs to be performed, and clinical judgment and careful discussion of pros and cons of treatment initiation need to be undertaken. For the majority of SMM patients, the standard of care remains observation until development of symptomatic MM occurs, encouraging participation in ongoing and upcoming SMM/early MM clinical trials, as well as consideration of bisphosphonate use in patients with early bone loss. © AlphaMed Press 2016.
Keywords: Progression; Risk Factors; Smoldering multiple myeloma; Treatment